Penguatan Branding Produk Madu Pada UMKM Madu YBS Melalui Media Website - Putu Yudy Wijaya; I Gede Putu Kawiana; I Gusti Ayu Wimba; I Made Astrama; Ni Putu Sri Hartati (JURNAL SEWAKA BHAKTI, 2022)
Honey is a unique product of insects, and is beneficial for health. MSME Honey YBS is a micro business that sells supply honey products from honey seekers at the foot of Mount Agung (Selat District, Karangasem Regency, Bali). Honey products sold by MSME Honey YBS have been marketed to several restaurants, but due to the COVID-19 pandemic and the temporary suspension of tourism activities, the demand for honey products has decreased drastically. MSME Madu YBS has limited promotional costs, and has not utilized online media which is currently widely used. Therefore, this community service aims to provide a website for YBS Honey SMEs. The website will be a medium for disseminating information about the business units and products of YBS Honey SMEs, and is equipped with a contact menu for the owner. Aside from being a promotional medium, this website will also help consumers who want to buy products, as well as other parties who plan to partner with MSME Madu YBS (product distributor). Through this community service activity, an understanding of the use of technology will be given to support MSME business activities.